Efta-barometer autumn 1992: Austria, Finland and Sweden - Gallup Europe (Gallup Europe, 1993)
The survey was carried out simultaneously in the three EFTA-countries Austria, Finland, and Sweden. In each country approximately 1 000 persons were asked about their opinions about a unified Western Europe, and personal interest in European Community matters. The respondent had to indicate how well informed she/he was about the EC, and if she/he had read or heard anything in mass media about the Single European Market and the ´European Economic Area´. Questions were asked about personal view on their own country participating in EEA, and about their country as a member of the EC, and if their country would benefit from a EC-membership. The respondent had to point out areas of policy which should be decided by the national government and areas of policy decided jointly within the European community. Furthermore the respondent had to indicate knowledge and attitude about the Maastricht Treaty. Questions were also asked about the future of the national identity within the EC, and if it will be replaced by a sense of European identity.

The survey was carried out simultaneously in the three EFTA-countries Austria, Finland, and Sweden. In each country approximately 1 000 persons were asked about their opinions about a unified Western Europe, and personal interest in European Community matters. The respondent had to indicate how well informed she/he was about the EC, and if she/he had read or heard anything in mass media about the Single European Market and the ´European Economic Area´. Questions were asked about personal view on their own country participating in EEA, and about their country as a member of the EC, and if their country would benefit from a EC-membership. The respondent had to point out areas of policy which should be decided by the national government and areas of policy decided jointly within the European community. Furthermore the respondent had to indicate knowledge and attitude about the Maastricht Treaty. Questions were also asked about the future of the national identity within the EC, and if it will be replaced by a sense of European identity.
Efta-barometer autumn 1992: Austria, Finland and Sweden
Keywords: NATIONAL IDENTITY; NATIONELL IDENTITET; EUROPEAN UNION; EUROPEISKA UNIONEN; EUROPEAN INTEGRATION; EUROPEISK INTEGRATION; INTERNAL POLITICS; INRIKESPOLITIK; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap